2017
DOI: 10.1007/s10014-017-0279-7
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological features of liponeurocytoma

Abstract: To discuss the clinicopathological features of liponeurocytoma, we retrospectively reviewed three liponeurocytoma cases and compared their immunophenotypes and genotypes with those of similar tumors. Furthermore, we reviewed the literature and compared the similarities and differences between cerebellar and intraventricular liponeurocytomas. Two cerebellar and one intraventricular liponeurocytomas were included in the present study. The liponeurocytomas comprised small tumor cells and lipomatous cells. The tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Epidemiology cLNCs are highly uncommon, benign, slow-growing glioneuronal neoplasms of the CNS with a favorable clinical prognosis, but a high likelihood of recurrence (1,9), which develop mainly in the adult population. The cerebellar hemisphere is the most common anatomical location for these tumors, followed by the cerebellar vermis, and the tumor can also occur in the supratentorial parenchyma (10,11,(14)(15)(16). Anghileri et al also reported a lumbar metastasis 11 years after the primary surgical excision (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiology cLNCs are highly uncommon, benign, slow-growing glioneuronal neoplasms of the CNS with a favorable clinical prognosis, but a high likelihood of recurrence (1,9), which develop mainly in the adult population. The cerebellar hemisphere is the most common anatomical location for these tumors, followed by the cerebellar vermis, and the tumor can also occur in the supratentorial parenchyma (10,11,(14)(15)(16). Anghileri et al also reported a lumbar metastasis 11 years after the primary surgical excision (14).…”
Section: Discussionmentioning
confidence: 99%
“…Rosette-like arrangements of tumor cells around the thin vessels were observed in other areas, which had features similar to cellular ependymoma. presented that the Ki-67 index had a tendency to increase after cLNCs recurrence, suggesting tumor progression with a tendency to malignant transformation (3,12,16). Immunostaining provides additional meaningful information that allows for correct diagnosis and differential diagnosis.…”
Section: Jouvet (12)/ 2005mentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, CLPN was composed of monotonous small round tumor cells and lipomatous cells [68]. Mitosis is rare or absent.…”
Section: Discussionmentioning
confidence: 99%
“…It shows a monotonous pattern of isomorphic round to oval cells with focal accumulations of lipid-laden cells. The lipomatous cells of the liponeurocytoma seem to be neuroepithelial tumor cells with lipid accumulation or they constitute a form of lipidization instead of true adipose cells [ 7 , 8 ]. In the lipomatous cells, the lipid vacuole membranes were positive for SYN, MAP-2, vimentin, and S-100.…”
Section: Discussionmentioning
confidence: 99%